PuReWidgets : a programming toolkit for interactive public display applications - Cardoso, Jorge C. S. (2012)
Interaction is repeatedly pointed out as a key enabling element towards more engaging and valuable public displays. Still, most digital public displays today do not support any interactive features. We argue that this is mainly due to the lack of efficient and clear abstractions that developers can use to incorporate interactivity into their applications. As a consequence, interaction represents a major overhead for developers, and users are faced with inconsistent interaction models across different displays. This paper describes the results of a study on interaction widgets for generalized interaction with public displays. We present PuReWidgets, a toolkit that supports multiple interaction mechanisms, automatically generated graphical interfaces, asynchronous events and concurrent interaction. This is an early effort towards the creation of a programming toolkit that developers can incorporate into their public display applications to support the interaction process across multiple display systems without considering the specifics of what interaction modality will be used on each particular display.